Stone cold Christmas ranger - Helm, Nicole (Don Mills, Ontario : Harlequin Enterprises, Ltd., 2017)
Bennet Stevens will do anything to prove himself. But the ranger never expected a cold case lead like Alyssa Jimenez, a wild-card bounty hunter. Or that someone would target her. The only safe place she can hide is in Bennet's elite world. But Alyssa's gutsy maneuvers and surprising vulnerability are putting Bennet's heart at passionate risk. Alyssa barely survived her drug-cartel family's machinations. She knows all too well that trusting anyone can get you dead. Still, Bennet is the only way she can finally put her mother's unsolved murder to rest. But posing as his lover is seductive and risky. And exposing the truth could guarantee they won't live to celebrate Christmas.
Keywords: Texas Rangers -- Fiction; Texas Rangers; Women bounty hunters -- Fiction; Cold cases (Criminal investigation) -- Fiction; FICTION -- Romance -- Suspense; FICTION -- Thrillers -- Suspense; FICTION -- Westerns; Christmas stories; Cold cases (Criminal investigation); Man-woman relationships; Women bounty hunters; Christmas stories; Christmas fiction; Fiction; Romance fiction; Western fiction; Romantic suspense fiction; Western stories; Romance fiction; Western fiction; Christmas fiction